Pengaruh Stakeholders dan Pengambilan Risiko Terhadap Kinerja Perusahaan Sektor Consumer Cyclicals - Marlia Putri Wuryanti; Wahyu Pramesti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine the influence of stakeholders and risk taking on company performance. This study was conducted on consumer cyclicals companies listed on the IDX in 2019-2023. The research sample was determined using a purposive sampling technique and obtained 50 companies with 250 observation data. The panel data regression analysis technique used the eviews 12 analysis tool. The results showed that the accounts receivable turnover ratio and current ratio had a positive effect on company performance. Then foreign ownership, ownership concentration, board of commissioners size, board of directors size, Human Capital Efficiency, Structural Capital Efficiency, and risk taking did not affect company performance.